Heroines of comic books and literature portrayals in popular culture - Bajac-Carter, Maja 1979-; Jones, Norma 1972-; Batchelor, Bob (Lanham, Maryland Rowman & Littlefield, 2014)
"In 'Heroines of comic books and Literature: Portrayals in Popular Culture,' editors Maja Bajac-Carter, Norma Jones, and Bob Batchelor have selected essays by award-winning contributors that offer a variety of perspectives on the representations of heroines in today's society. Focused on printed media, this collection looks at heroic women depicted in literature, graphic novels, manga, and comic books. Addressing heroines from such sources as the Marvel and DC comic universes, manga, and the Twilight novels, contributors go beyond the account of women as mothers, wives, warriors, goddesses, and damsels in distress."--From the publisher.
Literature : To heck with the village: fantastic heroines, journey and return / Sandra J. Lindow ; From duckling to swan: what makes a Twilight heroine strong / Tricia Clasen ; Salem's daughters: witchcraft, justice, and the heroine in popular culture / Lauren Lemley ; Heroine: Christina of Markyate / K. A. Laity ; The bohemian gypsy, another body to sell: deciphering Esmeralda in popular culture / Adina Scheewis ; Writing women in war: speaking through, about, and for female soldiers in Iraq / Christina M. Smith -- Exotic, foreign, familiar, and queer : The borderland construction of Latin America and Latina heroines in contemporary visual media / Mauricio Espinoza ; Janissary: an Orientalist heroine or a role model for Muslim women? / Itir Erhart and Hande Eslen-Ziya ; Representations of motherhood in X-Men / Christopher Paul Wagenheim ; Negotiating life spaces: how marriage marginalized Storm / Anita McDaniel ; The mother of all superheroes: idealizations of femininity in Wonder Woman / Sharon Zechowski and Caryn E. Neumann ; Wonder Woman: lesbian or dyke?: Paradise Island as a woman's community / Trina Robbins ; Homicidal lesbian terrorists to crimson caped crusaders: how folk and mainstread lesbian heroes queer cultural space / AprilJo Murphy -- Contemporary American graphic novels/comic : Punching holes in the sky: Carol Danvers and the potential of superheroinism / Nathan Miczo ; Jumping rope naked: John Byrne, metafiction, and the comics code / Roy Cook ; Invisible, tiny, and distant the powers and roles of Marvel's early female superheroes / Joseph Darowski ; Heroines aplenty, but none my mother would know: Marvel's lack of an iconic superheroine / T. Keith Edmunds ; Liminality and capitalism in Spider-Woman and Wonder Woman: how to make stronger (i.e. male) two super powerful women / Fernando Gabriel Pagnoni Berns ; Empowerment as transgression: the rise and fall of the Black Cat in Kevin Smith's The Evil That Men Do / Michael R. Kramer.
Includes bibliographical references and index.
Keywords: Women in literature; Heroines in literature; Women in popular culture; Women in mass media; Comic books, strips, etc. -- History and criticism